The role of sound doctrine in shaping human behavior and its impact on reforming the individual within the framework of sustainable development (College of Basic Education Research Journal, 2026)
This study aims to highlight the role of sound doctrine and its impact on guiding and correcting human behavior. Societies founded on correct thought exhibit human conduct that aligns with the innate moral nature with which humans were created. The importance of this research stems from the emergence of deviant and spread of superstitions among simple-minded individuals. The research seeks to serve as a source for opening a window of dialogue with the true divine religions, as they are responsible for correcting misguided ideas, liberating individuals from superstitions and immoral doctrinal deviations, and reviving social responsibility to protect future generations from such distortions. A society cannot thrive economically or socially without virtuous values and ethics, and these cannot be instilled or enforced without religious motivation and conscience. The study adopts a descriptive-analytical methodology, describing doctrinal cultures and analyzing the impact of these beliefs and ideas. The research concludes that doctrine has a significant influence on an individual's behavior and thinking, and that sound doctrine guides and corrects the individual in a balanced and upright manner.
Keywords: Doctrine; Individual Behavior; Society; Development; Sustainability